Pengaruh Self Control Terhadap Tingkat Prokrastinasi Akademik: A Systematic Literature Review (SLR) - Kalyaniti, Lalita; Nyanasuryanadi, Partono; Ditthisampanno, Budi Utomo; Wandi, Wandi; Mitta, Putriana (Innovative: Journal Of Social Science Research, 2025)
Students must complete academic tasks given by teachers at school. However, students have problems such as academic procrastination that usually arise when students complete the assigned tasks. The effect of self-control on student procrastination is the subject of this study. This study is a systematic literature review. The data synthesis process in this study was carried out by comparing ten literatures that met the quality and inclusion and exclusion criteria with the sources used, such as Google, Schoolar, and ScienceDirect. Based on the literature review that the researcher analyzed, the researcher can conclude that self-control has an influence on students' academic procrastination. Students who have high self-control will be better able to manage themselves, able to overcome problems or difficulties in doing the tasks given. Conversely, students who have low self-control will more often delay or procrastinate.